The reality of the libraries of children in the State of Kuwait and the difficulties it faces from the perspective of its employees - Al Harbi, Adel Khaled Nayef (Journal of Humanities & Social Sciences, 2017)
The purpose of this study was to determine the status quo of children libraries in the State of Kuwait and difficulties they face from the perspective of their librarians. The population of this study consisted of (85) librarians, working in eight children libraries, of whom (70) responded (82.3%). To achieve the objectives of the study, a questionnaire was constructed, consisting of three sections: The first, included demographic data about respondents, namely: sex, specialty, academic qualification, and years of experience. The second, consisted of (69) paragraphs related to the status quo of children libraries in the State of Kuwait, and included six dimensions: building and facilities, administration and human resources, information resources, organization of information resources, information services, and the use of technology. The third section, consisted of (25) paragraphs related to the difficulties faced by the children's libraries in the State of Kuwait. The questionnaire was tested for which validity and reliability. Findings indicated that the estimation of the status quo of children libraries in the State of Kuwait from librarians' perspective was intermediate, and that one domain: Organization of information resources was estimated high, while other domains were estimated intermediate. Results also revealed no significance differences at (α≤0.05) between means of librarians' perspective towards the status quo of children libraries in the State of Kuwait due to gender, specialization, academic qualification, and years of experience. Also they revealed that librarians estimated the difficulties children libraries face as intermediate, and that two obstacles were the most important: the general look of peoples responsible of those libraries as a repository for books, and the lack of awareness of parents on the importance of children libraries on the child personal development and integrity. Results also indicated no statistical significance differences at (α≤0.05) were found between means of librarians on their sense of feeling the difficulties their libraries face due to sex, speciality, academic qualification, and years of experience.
Keywords: children's libraries; children's library workers